Selection of the Use of Formwork in the Holiday Inn Bukit Randu Hotel Project Using the Fuzzy AHP Method - Fajarviani, Sc. Elan Lida; Usman, Kristianto; Winarsih, Anita Lestari Condro (International Journal of Aviation Science and Engineering - AVIA, 2022)
Along with the development of the construction world, formwork has also progressed from being assembled on site to being assembled first at the factory. In Indonesia, many types of formwork have been used, which each have their own advantages and disadvantages. In selecting the type of formwork used, many factors or criteria need to be considered. The purpose of this study is to determine the type of formwork that is relatively best for use in the Holiday Inn Bukit Randu Hotel Project by calculating the weight of the criteria, sub criteria, and also the alternatives used using the Fuzzy AHP Method. Based on the criteria and alternatives that have been compiled by the researcher, as well as the analysis carried out using the Fuzzy AHP method, it is known that metal (system) formwork is the relatively best formwork with the largest final weight of 43.6%, while semi-system formwork with a final weight of 24, 6% and conventional formwork by 31.8%. However, after being reviewed based on the cost aspect, the semi-system formwork is the relatively best formwork to be used in the Holiday Inn Bukit Randu Hotel Project.